Implementation Aesthetic of Architecture Deli Melayu Design of a Tiny Hotel in Medan City - Melly Andriana; Ramayana Ramayana; Zuraidah Tharo (Budapest International Research and Critics University, 2021)
The level of need for accommodation continues to increase every year based on the high level of mobility of tourists who travel practically and economically, especially after the impact of covid 19, so that many domestic tourists want to relieve fatigue during the lockdown, but there are still few who apply the design. hotel building architecture with local cultural preservation and culture. Tiny hotels are currently growing and developing rapidly in big cities due to the impact of covid 19 which has caused the lodging business to shake up in Indonesia. In this study, this phenomenon underlies the design of Tiny Hotels in Medan City with the Malay Deli architectural approach. The result of this research is the design of the Tiny hotel with a cultural approach to Malay Deli architecture that applies the characteristic principles of Malay architecture.